2022
DOI: 10.1002/pssa.202100683
|View full text |Cite
|
Sign up to set email alerts
|

Transparent, Low‐Impedance Inkjet‐Printed PEDOT:PSS Microelectrodes for Multimodal Neuroscience

Abstract: Transparent microelectrodes that facilitate simultaneous optical and electrophysiological interfacing are desirable tools for neuroscience. Electrodes made from transparent conductors such as graphene and indium tin oxide (ITO) show promise but are often limited by poor charge‐transfer properties. Herein, microelectrodes are demonstrated that take advantage of the transparency and volumetric capacitance of poly(3,4‐ethylenedioxythiophene) polystyrene sulfonate (PEDOT:PSS). Ring‐shaped microelectrodes are fabri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 63 publications
0
13
0
Order By: Relevance
“…Further, we demonstrated that the polyethylene terephthalate (PET) film, the transparent window material in the polymer skulls, can be used as a substrate to pattern inkjet‐printed transparent electrodes and interconnects. [ 31 ] Combining these capabilities, we developed the eSee‐Shell, a fully‐integrated transparent polymer skull with ten inkjet‐printed ECoG electrodes ( Figure ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Further, we demonstrated that the polyethylene terephthalate (PET) film, the transparent window material in the polymer skulls, can be used as a substrate to pattern inkjet‐printed transparent electrodes and interconnects. [ 31 ] Combining these capabilities, we developed the eSee‐Shell, a fully‐integrated transparent polymer skull with ten inkjet‐printed ECoG electrodes ( Figure ).…”
Section: Resultsmentioning
confidence: 99%
“…Printed PEDOT:PSS interconnects and electrodes were ≈200 nm thick, as previously reported. [ 31 ] The devices were encapsulated in Parylene‐C, and then, an oxygen plasma etch was used to create electrode contact openings in the Parylene‐C. The unique electrode geometry used in eSee‐Shells creates a low‐impedance and transparent interface by using a large volume of encapsulated PEDOT:PSS spread laterally around a small ≈50 µm contact site.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Further, most neuroscience laboratories require rapid and flexible design alterations to adapt to various experimental contexts, which is hard to achieve in traditional microfabrication procedures. To simplify the fabrication procedure, inkjet printing conductive materials such as silver nanoparticle inks [9] and conductive polymers like PEDOT:PSS [10] has been used to create flexible and reconfigurable ECoG electrode arrays. Currently, these approaches require expensive printers and still rely on specialized or microfabrication techniques to insulate the electrode [11].…”
Section: Introductionmentioning
confidence: 99%